2022
DOI: 10.3390/photonics9090667
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Photonic Hooks under Point-Source Illumination from Patchy Microcylinders

Abstract: Photonic hook (PH) is a new type of non-evanescent light beam with subwavelength curved structures. It has shown promising applications in super-resolution imaging and has the potential to be used in micromachining, optical trapping, etc. PHs are generally produced by illuminating mesoscale asymmetric particles with optical plane waves. In this work, we used the finite-difference time-domain (FDTD) method to investigate the PH phenomenon under point-source illumination. We found that the PHs can be effectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…4 Point source illumination can also be used to produce photonic hooks from patchy particles. 5 Here we reported the progress of using patchy particles for super-resolution imaging, and we showed that the performance of the imaging system can also be enhanced by coating microspheres with Al films. Using Al instead of Ag can significantly reduce the cost of fabrication, and facilities the commercialization of this technique.…”
Section: Introductionmentioning
confidence: 94%
“…4 Point source illumination can also be used to produce photonic hooks from patchy particles. 5 Here we reported the progress of using patchy particles for super-resolution imaging, and we showed that the performance of the imaging system can also be enhanced by coating microspheres with Al films. Using Al instead of Ag can significantly reduce the cost of fabrication, and facilities the commercialization of this technique.…”
Section: Introductionmentioning
confidence: 94%
“…There are different methods used to achieve a particle structure with broken symmetry. One approach involves designing a structure with a fixed refractive index distribution but an asymmetrical geometry, such as adding a triangular prism to the front of a cuboid [21,22] or coating a metal film onto part of a microcylinder [23]. The other method entails designing a structure with a symmetrical geometry but an inhomogeneous refractive index distribution, exemplified by Janus particles, cuboids cladded with cylinders, or hexagonal prisms [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, patchy microspheres with metallic surface coatings can block a portion of incoming light, resulting in an asymmetric illumination effect. Their capacity of PH generation has been theoretically and experimentally demonstrated [15], [16], [17]. One of the most important applications of PHs is in super-resolution imaging [18], [19].…”
Section: Introductionmentioning
confidence: 99%